Pengaruh Struktur Modal, Ukuran Perusahaan, Dan Profitabilitas Terhadap Nilai Perusahaan (Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2019) - Yohan Aditama Putra; Batista Sufa Kefi (Jurnal Ekonomi Manajemen Akuntansi, 2021)
This study aims to determine the effect of capital structure, firm size, and profitability on firm value. The population of this study is the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange during the 2016-2019 research period, totaling 26 companies. This study uses a purposive sampling method with a total sample of 13 companies which are manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange in 2016-2019. The analytical model used in this study is a multiple linear regression analysis model which was carried out with the help of the SPSS version 25.0 computer program for windows.